MANAJEMEN KEGIATAN EKSTRAKULIKULER DALAM PEMBENTUKAN KARAKTER DISIPLIN SISWA DI SDN BEJI II BEJI - Ana Fikrotruzzakiyah; Ahmad Thohirin; M. Furqon Wahyudi (Jurnal Manajemen Pendidikan, 2026)
Objective: This study aims to analyze the management of extracurricular activities in shaping students’ disciplinary character at SDN Beji II Beji, Pasuruan Regency. The issue of discipline among elementary school students has become a crucial concern as it directly relates to learning success and the early development of moral character. This research employs a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observations, and document analysis involving three teachers who are actively involved in managing extracurricular activities. Data were analyzed using the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing.The findings reveal four major themes: (1) extracurricular activity management at SDN Beji II is implemented collaboratively among the principal, teachers, and activity supervisors; (2) disciplinary values are internalized through practical experiences such as punctuality, responsibility, and adherence to activity rules; (3) limited facilities and parental support remain the main challenges in sustaining the program; and (4) institutional support and teacher communication serve as key success factors. The practical implications emphasize the importance of well-planned, participatory, and sustainable management of extracurricular activities to enhance students’ discipline culture in the school environment.